Bella's empowerment - why the twilight saga is not anti-feminist. - See, Shawn Kai Sheng. (2013)
In the past decade, besides the Harry Potter franchise by J.K. Rowling and the Fifty Shades of Grey trilogy by E.L. James that have taken the contemporary literary scene by storm, no other novels can arguably match up to the success of Stephenie Meyer’s Twilight series. Meyer’s compelling work is immensely popular among its young adult audience. The Twilight series spans four novels and focuses on the love story of Meyer’s female protagonist Isabella Swan (better known as Bella), and her vampire beau Edward Cullen. Charting the progress of the protagonists’ acquaintance right through to their marriage, the Twilight saga encompasses the numerous trials and tribulations that both Bella and Edward face and overcome in the search for their “perfect piece of … forever” (Breaking Dawn 754). What sets the Twilight saga apart from its contemporaries is how Meyer weaves her romance story with an amalgamation of vampire and werewolf traditions. Meyer delineates how caught in between the fantastical world of these mythical arch-enemies, Bella, a weak and hapless human, successfully navigates and plots her own path such that by the end of the series supernatural hostilities are buried and Bella is able to create her very own happily ever after.